Charge transport properties in functionalized triphenylene and coronene derivatives: a density functional study using different functionals. Issue 1 (22nd November 2021) - Chen, Ziran; Zhang, Yujin; Li, Yuan; Yu, Wenhao
Abstract: We have investigated computationally the effect of π-conjugated extension on the charge transfer properties of triphenylene and coronene; where we have added fused benzene or triazole rings in the parent molecule. The results showed that the six polycyclic aromatic hydrocarbons investigated are semiconductor molecules. The μ- values of molecules naphthotriphenylene (a1 ), tribenzocoronene (b1 ), and tristriazolecoronene (b2 ) were 1.5 to 21.5 times that of the corresponding μ+ values, suggesting that they are n-type organic semiconductors. Compared with the results obtained by the B3LYP and B3LYP + D3 methods, the charge transport mobility obtained using M06-2X, M06-2X + D3, and M08-HX showed the similar calculation results.